History of the English Language : Навчально-методичний посібник - Soloviova, Olga (My University, 2023)
Навчально-методичний посібник з курсу “Історія англійської мови” містить матеріали лекцій та семінарських занять, що мають на меті сформувати знання та компетентності студентів з питань розвитку та становлення англійської мови. Запропонований посібник призначено для студентів третього курсу факультету іноземних мов, що вивчають англійську мову як першу іноземну.
Theme 1. General Characteristics of the English Language Theme 2. Old English Extralinguistic Factors Theme 3. Phonological System of Old English Theme 4. Morphological System of the Old English Language Theme 5. Old English Lexicon Theme 6. Middle English Period: Extra- and Intralinguistic Factors Theme 7. The Phonological System of Middle English Theme 8. The Morphological System of Middle English Theme 9. Middle English Lexicon Theme 10. Early Modern English Period: Extra- and Intralinguistic Factors Theme 11. Early Modern English Phonology Theme 12. Early Modern English Morphology Theme 13. Early Modern English Lexis
Keywords: Old English; Middle English; Early Modern English